A comparative analysis of the projects undertaken in the development of a taxation framework in the digital economy - De Bruyn, Christoffel Wilhelmus (Department of Commercial Law, 2016)
The objective of this comparative paper is to analyse and compare the work undertaken by the OECD's TFDE and the DTC on the taxation of the digital economy in light of the overarching project on BEPS, with a view of analysing the possible application of the proposed options to address the tax challenges of the digital economy in the South African taxation framework.